Utilization of brewery wastes in food industry - Rachwał, Kamila; Waśko, Adam; Gustaw, Klaudia; Polak-Berecka, Magdalena (PeerJ, 2020)
Beer is the most popular low-alcohol beverage consumed in large amounts in many countries each year. The brewing industry is an important global business with huge annual revenues. It is profitable and important for the economies of many countries around the world. The brewing process involves several steps, which lead to fermentation of sugars contained in malt and conversion thereof into alcohol and carbon dioxide by yeasts. Beer brewing generates substantial amounts of by-products. The three main brewing industry wastes include brewer’s spent grain, hot trub, and residual brewer’s yeast. Proper management of these wastes may bring economical benefits and help to protect the environment from pollution caused by their excessive accumulation. The disposal of these wastes is cumbersome for the producers, however they are suitable for reuse in the food industry. Given their composition, they can serve as a low-cost and highly nutritional source of feed and food additives. They also have a potential to be a cheap material for extraction of compounds valuable for the food industry and a component of media used in biotechnological processes aimed at production of compounds and enzymes relevant for the food industry.
Keywords: Brewery by-products; Waste re-use; Brewer’s spent grain-based food products; Food products from wastes